ANALISIS RISIKO KEHILANGAN PASCA PANEN PADA RANTAI PASOK WORTEL DENGAN METODE HOUSE OF RISK (STUDI KASUS DI KABUPATEN MAGETAN) - Amilia, Winda; Jamalia Ulfa, Erlin; Suryaningrat, Ida Bagus; Suryadharma, Bertung (Jurnal Penelitian Sains dan Teknologi Indonesia, 2022)
Carrot as a vegetable is a food that has a fairly high level of losses in the distribution process. Actors involved in the carrot supply chain are farmers, agents, stall traders, mobile traders and consumers. The number of actors involved in the carrot supply chain will result in the risk of post-harvest losses that can affect the quality of carrots that consumers get. This study aims to analyze the risk of post-harvest losses and design a management strategy to reduce the incidence of carrot supply chain risk in Magetan District. The method used is the House of Risk which consists of 2 phases. The results showed that the types of mechanical damage that occurred in the carrot supply chain could be classified into abrasion, cracking, puncture, cutting, bruising, splitting, tearing, and skin cracking which were identified as risks caused by 15 risk agents. From the 15 risk agents obtained, 7 priority risk agents were selected and analyzed to determine the mitigation strategies that could be applied. The mitigation strategies obtained in this study were 6 mitigation strategies. With risk management and mitigation strategies in the carrot supply chain, it is expected to be able to minimize the risk of mechanical damage that occurs in the carrot supply chain in Magetan Regency.